Wykorzystanie detalicznej bankowości elektronicznej w zarządzaniu finansami osobistymi - Świecka, Beata (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The purpose of the study is to analyze and evaluate usage of electronic bankingin personal finances’ management. In the paper the following hypothesis isverified: Retail e-banking offers tools to help manage personal finances and thusfacilitates the entire management process, however financial literacy is essentialas it gives direction to the activities in the field of financial management.